Left Anterior Temporal Lobe and Bilateral Anterior Cingulate Cortex Are Semantic Hub Regions: Evidence from Behavior-Nodal Degree Mapping in Brain-Damaged Patients - Zhao, Ying (J Neurosci, 2017)
The organizational principles of semantic memory in the human brain are still controversial. Although studies have shown that the semantic system contains hub regions that bind information from different sensorimotoric modalities to form concepts, it is unknown whether there are hub regions other than the anterior temporal lobe (ATL). Meanwhile, previous studies have rarely used network measurements to explore the hubs or correlated network indexes with semantic performance, although the most direct supportive evidence of hubs should come from the network perspective. To fill this gap, we correlated the brain-network index with semantic performance in 86 brain-damaged patients. We especially selected the nodal degree measure that reflects how well a node is connected in the network. The measure was calculated as the total number of connections of a given node with other nodes in the resting-state functional MRI network. Semantic ability was measured using the performance of both general and modality-specific (object form, color, motion, sound, manipulation, and function) semantic tasks. We found that the left ATL and the bilateral anterior cingulate cortex could be semantic hubs because the reduced nodal degree values of these regions could effectively predict the deficits in both general and modality-specific semantic performance. Moreover, the effects remained when the analyses were performed only in the patients who did not have lesions in these regions. The two hub regions might support semantic representations and executive control processes, respectively. These data provide empirical evidence for the distributed-plus-hub theory of semantic memory from the network perspective. SIGNIFICANCE STATEMENT Although the distributed-plus-hub organization of semantic memory has been proposed for several years, it remains unclear which hubs other than the anterior temporal lobe are included in the semantic system. Here, we identified such hubs from an innovative network perspective. The voxelwise nodal degree values were correlated with the performance of general and modality-specific semantic tasks in 86 patients with brain damage. We observed that the left anterior temporal lobe and bilateral anterior cingulate cortex could be semantic hubs because their decreased nodal degree values were significantly correlated with the severity of the deficit in semantic performance. The two hub regions might contribute to semantic representational and control processes, respectively. These findings offer new evidence for the distributed-plus-hub theory.